EVA two-color integrated injection foaming material and preparation method thereof
By using specific component ratios and preparation methods in EVA foaming materials, EVA two-color integrated molding ejection foaming materials are prepared, which solves the problem that existing materials are difficult to have both tensile strength and compression resilience performance, and achieves excellent results material properties.
Patent Information
- Application Number
- CN202411514136.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-10-29
AI Technical Summary
It is difficult for existing EVA foaming materials to combine good tensile strength and compression rebound performance.
EVA two-color integrated molding spray foaming material is adopted, and through specific component ratios and preparation methods, including EVA, polyadipate butadipate terephthalate, AC foaming agent, zinc oxide, dodecyl trimethyl Ammonium chloride, modified composite calcium carbonate, diapropyl peroxide, water, masterbenzene and zinc stearate were prepared by a combined process of twin-screw extrusion and injection molding equipment.
The excellent tensile strength and compression rebound performance of the EVA two-color integrated molding foamed material are achieved, and the overall performance of the material is improved.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the field of polymer composite materials, and in particular to an EVA two-color integrated injection foaming material and a preparation method thereof. Background Art
[0002] Ethylene-vinyl acetate copolymer (EVA) is a rubber-like thermoplastic, which has excellent flexibility, low-temperature flexibility, elasticity, stress cracking resistance, good plasticity and processability compared with polyethylene, and is therefore widely used. The application field of EVA is quite extensive, and EVA foam material has the properties of softness, good elasticity, chemical resistance, etc., and is applied to the soles and interior materials of mid-to-high-end tourist shoes, mountaineering shoes, slippers, and sandals. However, existing EVA foam materials are difficult to have good tensile strength and compression resilience. Summary of the invention
[0003] In view of this, an object of the present invention is to provide an EVA two-color one-piece injection foaming material and a preparation method thereof, wherein the prepared two-color one-piece injection foaming material has excellent tensile strength and compression rebound performance.
[0004] In order to achieve the above-mentioned object, the present invention provides the following technical scheme: an EVA two-color one-piece injection foaming material, comprising the following components in parts by weight: 30-40 parts of EVA, 10-20 parts of polybutylene adipate terephthalate, 6-8 parts of AC foaming agent, 12-16 parts of zinc oxide, 5-8 parts of dodecyltrimethylammonium chloride, 20-30 parts of modified composite calcium carbonate, 2-4 parts of dicumyl peroxide, 60-80 parts of water, 1-5 parts of a first color masterbatch, 1-5 parts of a second color masterbatch and 1-2 parts of zinc stearate.
[0005] Preferably, the EVA two-color one-piece injection foaming material includes the following components in parts by weight: 35 parts of EVA, 15 parts of polybutylene adipate terephthalate, 7 parts of AC foaming agent, 14 parts of zinc oxide, 6.5 parts of dodecyltrimethylammonium chloride, 25 parts of modified composite calcium carbonate, 3 parts of dicumyl peroxide, 70 parts of water, 3 parts of first color masterbatch, 3 parts of second color masterbatch and 1.5 parts of zinc stearate.
[0006] The present invention also provides a method for preparing an EVA two-color one-piece injection foaming material, which is used to prepare the EVA two-color one-piece injection foaming material, comprising the following steps:
[0007] Step 1, uniformly mix EVA, polybutylene adipate terephthalate, AC foaming agent, zinc oxide, dodecyltrimethylammonium chloride, modified composite calcium carbonate, dicumyl peroxide, water, the first color masterbatch and zinc stearate in half parts by weight, stir for 20-30 minutes, add into the hopper of a twin-screw extruder for melt extrusion, and obtain a first unfoamed material;
[0008] Step 2, uniformly mix the remaining half weight portion of EVA, polybutylene adipate terephthalate, AC foaming agent, zinc oxide, dodecyltrimethylammonium chloride, modified composite calcium carbonate, dicumyl peroxide, water, the second color masterbatch and zinc stearate, stir for 20-30 minutes, add into the hopper of a twin-screw extruder for melt extrusion, and obtain a second unfoamed material;
[0009] Step 3: suck the first unfoamed material and the second unfoamed material into the injection molding device respectively, and then inject them into the mold cavity in sequence through two injection guns of the injection molding device to obtain the EVA two-color one-piece injection foamed material.
[0010] Preferably, the preparation method of the modified composite calcium carbonate specifically comprises the following steps:
[0011] S1: preparing adhesive and modified enzymatic lignin respectively;
[0012] S2: Mix the adhesive, modified enzymatic lignin, calcium carbonate and N,N-dimethylformamide in a weight ratio of 1:1:1:10, stir magnetically at 45-55°C for 1-2h and then dry to obtain modified composite calcium carbonate.
[0013] Preferably, the preparation method of the adhesive specifically comprises the following steps:
[0014] S11: In an inert gas atmosphere, 4,4'-diaminostilbene-2,2'-disulfonic acid, m-cresol and triethylamine are mixed uniformly, and reacted at 60-80° C. for 6-8 hours to obtain a reaction mixture;
[0015] S12: Mix the reaction mixture, 1,4,5,8-naphthalenetetracarboxylic anhydride, 4,4'-bis(4-aminophenoxy)diphenyl sulfone and benzoic acid, and react at 160-180° C. for 6-8 hours to obtain an adhesive.
[0016] Preferably, in step S11, the weight ratio of 4,4'-diaminostilbene-2,2'-disulfonic acid, m-cresol and triethylamine is 1:3:4.
[0017] Preferably, the weight ratio of the reaction mixture, 1,4,5,8-naphthalenetetracarboxylic anhydride, 4,4'-bis(4-aminophenoxy)diphenyl sulfone and benzoic acid is 1:2:3:5.
[0018] Preferably, the preparation method of the modified enzymatic lignin is:
[0019] Maleic anhydride, enzymatic lignin and 40% by mass sodium hydroxide solution are mixed, stirred for 2-4 hours, and then dried at 60-70° C. under vacuum for 24 hours to obtain modified enzymatic lignin.
[0020] Preferably, the weight ratio of the maleic anhydride, enzymatically hydrolyzed lignin and sodium hydroxide solution is 1:1:4.
[0021] Preferably, the temperatures of the five heating zones of the twin-screw extruder are 60° C., 70° C., 75° C., 85° C., and 90° C., respectively, and the screw speed is 14-16 r / min.
[0022] Preferably, the three temperature sections of the material pipe of the shooting gun are 175°C, 185°C and 200°C respectively.
[0023] The invention has the following beneficial effects: the invention grafts the sulfonic acid and amide groups through long flexible chain segments onto the sulfonated polyimide groups through the strong hydrogen bonding of the sulfonic acid and amide groups, and uses the sulfonated groups as cross-linking points. Meanwhile, the molecules of lignin contain many hydroxyl groups and benzene rings, and the hydrogen bonds between the hydroxyl groups, combined with the introduced cross-linking points of the sulfonated groups, can form stronger conjugation between the molecular chains, so that the foaming agent and calcium carbonate are adsorbed and bonded to the surface of the composite chain structure polymer, thereby improving the dispersibility and uniformity of the long flexible chain segments, and increasing the specific surface areas of the foaming agent and calcium carbonate, promoting the increase of the free volume of the composite chain structure polymer, thereby reducing the stress concentration in the foaming process during the foaming and bubbling process, and improving the molecular chain movement ability, so as to improve the compression performance and rebound performance of the foaming material. DETAILED DESCRIPTION
[0024] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. In addition, it is specifically stated that the raw materials and equipment of the present invention can be obtained from commercial sources, and no longer listed one by one. Among them, the raw materials of the present invention can be obtained from commercial sources and are well known to those skilled in the art.
[0025] Embodiment 1: An EVA two-color one-piece injection foaming material comprises the following components in parts by weight: 40 parts of EVA, 20 parts of polybutylene adipate terephthalate, 8 parts of AC foaming agent, 16 parts of zinc oxide, 8 parts of dodecyl trimethyl ammonium chloride, 30 parts of modified composite calcium carbonate, 4 parts of dicumyl peroxide, 80 parts of water, 5 parts of the first masterbatch, 5 parts of the second masterbatch and 2 parts of zinc stearate. The first masterbatch and the second masterbatch have different colors, for example, the first masterbatch is red masterbatch particles, and the second masterbatch is blue masterbatch particles.
[0026] This embodiment also provides a method for preparing an EVA two-color one-piece injection foaming material, which is used to prepare the EVA two-color one-piece injection foaming material, comprising the following steps:
[0027] Step 1, EVA, polybutylene adipate terephthalate, AC foaming agent, zinc oxide, dodecyltrimethylammonium chloride, modified composite calcium carbonate, dicumyl peroxide, water, the first color masterbatch and zinc stearate, which are respectively half parts by weight, are uniformly mixed and stirred for 30 minutes, and added into the hopper of a twin-screw extruder for melt extrusion, wherein the temperatures of the five heating zones of the twin-screw extruder are 60° C., 70° C., 75° C., 85° C. and 90° C., respectively, and the screw speed is 16 r / min, to obtain a first unfoamed material;
[0028] Step 2: Evenly mix the remaining half weight portion of EVA, polybutylene adipate terephthalate, AC foaming agent, zinc oxide, dodecyltrimethylammonium chloride, modified composite calcium carbonate, dicumyl peroxide, water, the second color masterbatch and zinc stearate, stir for 30 minutes, add them into the hopper of a twin-screw extruder for melt extrusion, the temperatures of the five heating zones of the twin-screw extruder are 60° C., 70° C., 75° C., 85° C. and 90° C., respectively, and the screw speed is 16 r / min, to obtain a second unfoamed material;
[0029] Step 3: Suck the first unfoamed material and the second unfoamed material into the injection molding equipment respectively, and then inject them into the mold cavity in sequence through the two shooting guns of the injection molding equipment. The three-section temperatures of the material pipe of the shooting gun are 175°C, 185°C, and 200°C respectively, to obtain the EVA two-color one-piece injection foamed material.
[0030] In this embodiment, the preparation method of the modified composite calcium carbonate specifically includes the following steps:
[0031] S1: preparing adhesive and modified enzymatic lignin respectively;
[0032] The preparation method of the adhesive specifically comprises the following steps:
[0033] S11: In an inert gas atmosphere, 4,4'-diaminostilbene-2,2'-disulfonic acid, m-cresol and triethylamine were mixed uniformly in a weight ratio of 1:3:4, and reacted at 80° C. for 6 h to obtain a reaction mixture;
[0034] S12: mixing the reaction mixture, 1,4,5,8-naphthalenetetracarboxylic anhydride, 4,4'-bis(4-aminophenoxy)diphenyl sulfone and benzoic acid in a weight ratio of 1:2:3:5, and reacting at 180° C. for 6 hours to obtain an adhesive;
[0035] Wherein, the preparation method of the modified enzymatic lignin is:
[0036] Maleic anhydride, enzymatic lignin and 40% sodium hydroxide solution by weight were mixed in a weight ratio of 1:1:4, stirred for 4 hours, and dried at 70°C under vacuum for 24 hours to obtain modified enzymatic lignin;
[0037] S2: Mix the adhesive, modified enzymatic lignin, calcium carbonate and N,N-dimethylformamide in a weight ratio of 1:1:1:10, stir magnetically at 55° C. for 1 h and then dry to obtain modified composite calcium carbonate.
[0038] Embodiment 2: An EVA two-color one-piece injection foaming material includes the following components in parts by weight: 30 parts of EVA, 10 parts of polybutylene adipate terephthalate, 6 parts of AC foaming agent, 12 parts of zinc oxide, 5 parts of dodecyl trimethyl ammonium chloride, 20 parts of modified composite calcium carbonate, 2 parts of dicumyl peroxide, 60 parts of water, 1 part of the first masterbatch, 1 part of the second masterbatch and 1 part of zinc stearate. The first masterbatch and the second masterbatch have different colors, for example, the first masterbatch is red masterbatch particles, and the second masterbatch is blue masterbatch particles.
[0039] This embodiment also provides a method for preparing an EVA two-color one-piece injection foaming material, which is used to prepare the EVA two-color one-piece injection foaming material, comprising the following steps:
[0040] Step 1, EVA, polybutylene adipate terephthalate, AC foaming agent, zinc oxide, dodecyltrimethylammonium chloride, modified composite calcium carbonate, dicumyl peroxide, water, the first color masterbatch and zinc stearate are mixed evenly and stirred for 20 minutes, and then added into the hopper of a twin-screw extruder for melt extrusion, wherein the temperatures of the five heating zones of the twin-screw extruder are 60° C., 70° C., 75° C., 85° C. and 90° C., respectively, and the screw speed is 14 r / min, to obtain a first unfoamed material;
[0041] Step 2: Evenly mix the remaining half weight portion of EVA, polybutylene adipate terephthalate, AC foaming agent, zinc oxide, dodecyltrimethylammonium chloride, modified composite calcium carbonate, dicumyl peroxide, water, the second color masterbatch and zinc stearate, stir for 20 minutes, add them into the hopper of a twin-screw extruder for melt extrusion, the temperatures of the five heating zones of the twin-screw extruder are 60° C., 70° C., 75° C., 85° C. and 90° C., respectively, and the screw speed is 14 r / min, to obtain a second unfoamed material;
[0042] Step 3: Suck the first unfoamed material and the second unfoamed material into the injection molding equipment respectively, and then inject them into the mold cavity in sequence through the two shooting guns of the injection molding equipment. The three-section temperatures of the material pipe of the shooting gun are 175°C, 185°C, and 200°C respectively, to obtain the EVA two-color one-piece injection foamed material.
[0043] In this embodiment, the preparation method of the modified composite calcium carbonate specifically includes the following steps:
[0044] S1: preparing adhesive and modified enzymatic lignin respectively;
[0045] The preparation method of the adhesive specifically comprises the following steps:
[0046] S11: In an inert gas atmosphere, 4,4'-diaminostilbene-2,2'-disulfonic acid, m-cresol and triethylamine were mixed uniformly in a weight ratio of 1:3:4, and reacted at 60° C. for 8 h to obtain a reaction mixture;
[0047] S12: mixing the reaction mixture, 1,4,5,8-naphthalenetetracarboxylic anhydride, 4,4'-bis(4-aminophenoxy)diphenyl sulfone and benzoic acid in a weight ratio of 1:2:3:5, and reacting at 160° C. for 8 hours to obtain an adhesive;
[0048] Wherein, the preparation method of the modified enzymatic lignin is:
[0049] Maleic anhydride, enzymatic lignin and 40% sodium hydroxide solution by weight were mixed in a weight ratio of 1:1:4, stirred for 2 hours, and dried at 60°C under vacuum for 24 hours to obtain modified enzymatic lignin;
[0050] S2: The adhesive, modified enzymatic lignin, calcium carbonate and N,N-dimethylformamide were mixed in a weight ratio of 1:1:1:10, and the mixture was magnetically stirred at 45° C. for 2 h and then dried to obtain modified composite calcium carbonate.
[0051] Embodiment 3: An EVA two-color one-piece injection foaming material comprises the following components in parts by weight: 35 parts of EVA, 15 parts of polybutylene adipate terephthalate, 7 parts of AC foaming agent, 14 parts of zinc oxide, 6.5 parts of dodecyl trimethyl ammonium chloride, 25 parts of modified composite calcium carbonate, 3 parts of dicumyl peroxide, 70 parts of water, 3 parts of the first masterbatch, 3 parts of the second masterbatch and 1.5 parts of zinc stearate. The first masterbatch and the second masterbatch have different colors, for example, the first masterbatch is red masterbatch particles, and the second masterbatch is blue masterbatch particles.
[0052] This embodiment also provides a method for preparing an EVA two-color one-piece injection foaming material, which is used to prepare the EVA two-color one-piece injection foaming material, comprising the following steps:
[0053] Step 1, EVA, polybutylene adipate terephthalate, AC foaming agent, zinc oxide, dodecyltrimethylammonium chloride, modified composite calcium carbonate, dicumyl peroxide, water, the first color masterbatch and zinc stearate, which are respectively one-half weight parts, are mixed evenly and stirred for 25 minutes, and added into the hopper of a twin-screw extruder for melt extrusion, wherein the temperatures of the five heating zones of the twin-screw extruder are 60° C., 70° C., 75° C., 85° C. and 90° C., respectively, and the screw speed is 15 r / min, to obtain a first unfoamed material;
[0054] Step 2: Evenly mix the remaining half of the weight of EVA, polybutylene adipate terephthalate, AC foaming agent, zinc oxide, dodecyltrimethylammonium chloride, modified composite calcium carbonate, dicumyl peroxide, water, the second color masterbatch and zinc stearate, stir for 25 minutes, add them into the hopper of a twin-screw extruder for melt extrusion, the temperatures of the five heating zones of the twin-screw extruder are 60° C., 70° C., 75° C., 85° C. and 90° C., respectively, and the screw speed is 15 r / min, to obtain a second unfoamed material;
[0055] Step 3: Suck the first unfoamed material and the second unfoamed material into the injection molding equipment respectively, and then inject them into the mold cavity in sequence through the two shooting guns of the injection molding equipment. The three-section temperatures of the material pipe of the shooting gun are 175°C, 185°C, and 200°C respectively, to obtain the EVA two-color one-piece injection foamed material.
[0056] In this embodiment, the preparation method of the modified composite calcium carbonate specifically includes the following steps:
[0057] S1: preparing adhesive and modified enzymatic lignin respectively;
[0058] The preparation method of the adhesive specifically comprises the following steps:
[0059] S11: In an inert gas atmosphere, 4,4'-diaminostilbene-2,2'-disulfonic acid, m-cresol and triethylamine were mixed uniformly in a weight ratio of 1:3:4, and reacted at 70° C. for 7 h to obtain a reaction mixture;
[0060] S12: mixing the reaction mixture, 1,4,5,8-naphthalenetetracarboxylic anhydride, 4,4'-bis(4-aminophenoxy)diphenyl sulfone and benzoic acid in a weight ratio of 1:2:3:5, and reacting at 170° C. for 7 hours to obtain an adhesive;
[0061] Wherein, the preparation method of the modified enzymatic lignin is:
[0062] Maleic anhydride, enzymatic lignin and 40% sodium hydroxide solution by weight were mixed in a weight ratio of 1:1:4, stirred for 3 hours, and dried at 65°C under vacuum for 24 hours to obtain modified enzymatic lignin;
[0063] S2: Mix the adhesive, modified enzymatic lignin, calcium carbonate and N,N-dimethylformamide in a weight ratio of 1:1:1:10, stir magnetically at 50° C. for 1.5 h and then dry to obtain modified composite calcium carbonate.
[0064] Comparative Example 1: The difference from Example 3 is that calcium carbonate is used to replace the modified composite calcium carbonate.
[0065] Comparative Example 2: The difference from Example 3 is that no modified composite calcium carbonate is added.
[0066] The tensile strength and compression deformation tests were performed on the products prepared in Examples 1-3 and Comparative Examples 1-2. The test results are shown in Table 1.
[0067] Among them, the tensile strength test method: the tensile strength of the material is tested according to GB / T 6344-2008, the specimen is dumbbell-shaped, and the tensile speed is 500mm / min;
[0068] Compression set test method: According to HG / T 2876-2009 test material compression set, the sample is cut into a size of 20mm*20mm*10mm, the compression rate is 50%, the temperature is 50℃, and the time is 6h.
[0069] Table 1 Test data of the foaming materials of Examples 1-3 and Comparative Example 1:
[0070]
[0071] It can be seen from Table 1 that the EVA two-color one-piece injection foaming material prepared by the present invention has excellent tensile strength and compression rebound performance.
[0072] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. An EVA two-color one-piece injection foaming material, characterized in that: The invention comprises the following components in parts by weight: 30-40 parts of EVA, 10-20 parts of polybutylene adipate terephthalate, 6-8 parts of AC foaming agent, 12-16 parts of zinc oxide, 5-8 parts of dodecyltrimethylammonium chloride, 20-30 parts of modified composite calcium carbonate, 2-4 parts of dicumyl peroxide, 60-80 parts of water, 1-5 parts of first color masterbatch, 1-5 parts of second color masterbatch and 1-2 parts of zinc stearate; The preparation method of the modified composite calcium carbonate is specifically The following steps are involved: S1: preparing adhesive and modified enzymatic lignin respectively; S2: Mix the adhesive, modified enzymatic lignin, calcium carbonate and N,N-dimethylformamide in a weight ratio of 1:1:1:10, stir magnetically for 1-2 hours at 45-55° C., and then dry to obtain modified composite calcium carbonate; The preparation method of the adhesive specifically comprises the following steps: S11: In an inert gas atmosphere, 4,4'-diaminostilbene-2,2'-disulfonic acid, m-cresol and triethylamine are mixed uniformly, and reacted at 60-80° C. for 6-8 hours to obtain a reaction mixture; the weight ratio of the 4,4'-diaminostilbene-2,2'-disulfonic acid, m-cresol and triethylamine is 1:3:4; S12: mixing the reaction mixture, 1,4,5,8-naphthalenetetracarboxylic anhydride, 4,4'-bis(4-aminophenoxy)diphenyl sulfone and benzoic acid, and reacting at 160-180° C. for 6-8 hours to obtain an adhesive; the weight ratio of the reaction mixture, 1,4,5,8-naphthalenetetracarboxylic anhydride, 4,4'-bis(4-aminophenoxy)diphenyl sulfone and benzoic acid is 1:2:3:5; The preparation method of the modified enzymatic lignin is: Maleic anhydride, enzymatic lignin and 40% by mass sodium hydroxide solution are mixed, stirred for 2-4 hours, and then dried at 60-70° C. under vacuum for 24 hours to obtain modified enzymatic lignin; the weight ratio of the maleic anhydride, enzymatic lignin and sodium hydroxide solution is 1:1:
4.
2. The EVA two-color one-piece injection foam material according to claim 1, characterized in that: The invention comprises the following components in parts by weight: 35 parts of EVA, 15 parts of polybutylene adipate terephthalate, 7 parts of AC foaming agent, 14 parts of zinc oxide, 6.5 parts of dodecyltrimethylammonium chloride, 25 parts of modified composite calcium carbonate, 3 parts of dicumyl peroxide, 70 parts of water, 3 parts of first color masterbatch, 3 parts of second color masterbatch and 1.5 parts of zinc stearate.
3. A method for preparing an EVA two-color one-piece injection foaming material, used to prepare the EVA two-color one-piece injection foaming material as claimed in claim 1, characterized in that: The following steps are involved: Step 1, uniformly mix EVA, polybutylene adipate terephthalate, AC foaming agent, zinc oxide, dodecyltrimethylammonium chloride, modified composite calcium carbonate, dicumyl peroxide, water, the first color masterbatch and zinc stearate in half parts by weight, stir for 20-30 minutes, add into the hopper of a twin-screw extruder for melt extrusion, and obtain a first unfoamed material; Step 2, uniformly mix the remaining half weight portion of EVA, polybutylene adipate terephthalate, AC foaming agent, zinc oxide, dodecyltrimethylammonium chloride, modified composite calcium carbonate, dicumyl peroxide, water, the second color masterbatch and zinc stearate, stir for 20-30 minutes, add into the hopper of a twin-screw extruder for melt extrusion, and obtain a second unfoamed material; Step 3: suck the first unfoamed material and the second unfoamed material into the injection molding device respectively, and then inject them into the mold cavity in sequence through two injection guns of the injection molding device to obtain the EVA two-color one-piece injection foamed material.
4. The method for preparing the EVA two-color integrally formed injection foam material according to claim 3, characterized in that: The temperatures of the five heating zones of the twin-screw extruder are 60°C, 70°C, 75°C, 85°C, and 90°C, respectively, and the screw speed is 14-16r / min; the temperatures of the three sections of the material pipe of the shooting gun are 175°C, 185°C, and 200°C, respectively.
Citation Information
Patent Citations
High-elastic wear-resistant double-color EVA sole material and preparation method thereof
CN117820754A